The marketing strategy of Rajah Court Hotel focusing on promotion strategy / Magdalena Agan - Agan, Magdalena (2001)
This research attempts to study on the Promotion strategy done by Rajah Court Hotel (RCH) in promoting Rajah Court Hotel. Being purely for academic purposes, the study undertaken hopes to overcome the low occupancy rate during outside peak period, and to design a promotion strategy that will make Rajah Court Hotel a three star-rated hotel one ofthe most value for money and which leads Rajah Court Hotel to be the customers’ first choice hotel. The main objectives of this research are to analyse the effectiveness of RCH current promotion strategy in terms of strengths as to promote demand outside peak period for its hospitality services and food and beverages and to provide prompt and excellent services as to satisfy customers needs and wants. The data and information were collected via primary data and secondary data. About 150 questionnaires were distributed via cluster sampling method to get the respondents views, comments and feedback. 100 questionnaires were distributed to RCH guests and 46 questionnaires were answered.